Asosiasi Surat Kabar Digital terhadap Minat Membaca Koran Masyarakat di Kota Makassar - Saleh, Muhammad Akbar; Nahdiana, Nahdiana (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2023)
The purpose of this study was to determine the effect of digital newspapers on community newspaper reading interest in Tamalanrea Indah Village, Tamalanrea District, Makassar City. The research method used is quantitative method by distributing questionnaires and analyzed using SPSS. The results of this study indicate that Digital Newspapers have a significant influence on Reading Interest in the community in Tamalanrea Indah Village, Tamalanrea District, Makassar City, with tcount = 4.711> ttable = 1.984 and significance 0.000 <0.05. In the reliability test of variable X stated with Cronbach alpha value is 0.734 and variable Y is 0.702. And based on the coefficient of determination which shows that there is an association of Digital Newspapers and people's newspaper reading interest. It predicted approximately 0.185 or 18.5% of reading interest.